2004
DOI: 10.1097/01.jom.0000141658.91805.47
|View full text |Cite
|
Sign up to set email alerts
|

Violence in Healthcare Facilities: Lessons From the Veterans Health Administration

Abstract: Although work in health care is associated with high rates of assaults, closer scrutiny suggests specific possible intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 16 publications
4
51
1
2
Order By: Relevance
“…It may be that nurses can predict and manage tense situations better as their experience increases. However, the findings of Hodgson et al [23] conflict with this; they reported that nurses who had more than 20 years of experience were exposed to more violence. The difference is likely due to the fact that they examined the lifetime incidence of workplace violence, not just a 12-month period, and those who had worked longer would be expected to have experienced more violent events.…”
Section: Discussioncontrasting
confidence: 46%
“…It may be that nurses can predict and manage tense situations better as their experience increases. However, the findings of Hodgson et al [23] conflict with this; they reported that nurses who had more than 20 years of experience were exposed to more violence. The difference is likely due to the fact that they examined the lifetime incidence of workplace violence, not just a 12-month period, and those who had worked longer would be expected to have experienced more violent events.…”
Section: Discussioncontrasting
confidence: 46%
“…1,2 Briefly, these techniques involved advertisement to all employees in VHA by e-mail messages and bulletin boards. Employees received e-mails and e-mail reminders with a link to the survey instrument, and local coordinators supported administration.…”
Section: Methodsmentioning
confidence: 99%
“…5,7,21,24,25 In novel findings, increasing hours worked in the public and NGO sector were weakly associated with external aggression, negatively for males but positively for females, whereas for internal aggression increasing hours worked in private practice for both males and females was weakly protective for aggression exposure. In addition, for male clinicians, having a poor support network of other doctors was positively associated with external aggression, whereas for both male and female clinicians, having a poor support network of other doctors was positively associated with internal aggression.…”
Section: Sex Differences In Aggression In Medical Work Australian Heamentioning
confidence: 89%